(untitled) (Damascus University Journal for the economic and Political sciences, 2024)
Job burnout has received increasing attention from researchers because of its negative effects and the challenges it poses to individuals and organizations. this research highlights the impact of the dimensions of psychological capital on the dimensions of job burnout and analyzes the mediating role of job insecurity in this relationship, the impact of job insecurity has been studied. The dimensions of psychological capital in the dimensions of job burnout, and the nature of the mediating role of job insecurity in this relationship, and through a simple random sample of volunteers in humanitarian organizations amounting to (280 individuals). The research was analyzed statistically using the AMOS V.26. The research analysis statistically resulted in a negative effect of the dimensions of psychological capital on the two dimensions of job burnout (emotional exhaustion, depersonalization) and a positive effect on (personal accomplishment), and a negative moral effect of the dimensions of psychological capital on job insecurity. The results also resulted in Research shows that job insecurity has a partial mediating role in the relationship between the dimensions of psychological capital and the dimensions of job burnout.